Dimension of Human Perfection Based on the Quran - Yusuf, Muhammad; Nahdhiyah, Nahdhiyah; Suardi Wekke, Ismail (Opción, 2019)
The aim of the study is to investigate dimension of humanperfection based on the Quran via comparative qualitative researchmethod. As a result, using many different words to designate oneobject gives an indication of different contents within it. For thisreason, a thematic-comprehensive study of the concept of the Quran isneeded to describe human being as a whole. In conclusion, every termused by the Quran to explain humanity gives a picture of the humandimension and the whole term used by the Quran which designateshuman meaning as a separate entity.